Regional multilingualisms and language teaching in indigenous schools in Mexico - Muñoz Cruz, Héctor (Árboles y Rizomas, 2025)
Humanity is experiencing a global cultural and sociolinguistic reorganization expressed in open societies that evidence great mobility and inequalities. In this context, the phenomenon of multilingualism represents a space of change that impacts all social domains. This paper outlines this situation in language teaching and learning in Indigenous school education in Mexico, with abundant "informal" communicative practices based on the natural learning of Indigenous adults and children of a dominant diglossic and asymmetric multilingualism promoted by migratory flows that favor hegemony of Spanish and, to a lesser extent, English. This text presents results of a sociolinguistic investigation that promoted the use of community multilingualism in two relevant pedagogical functions in language teaching: preparatory and organizational stage of the school group for the language class and the construction of cognitions about language. This experience employed the pragmatic category of "communicative school action cycle," a unit of analysis in the microethnography of educational communication, to identify, interpret, and intervene the qualitative and time-based action structures and cycles of communicative tasks in a language class (Gumperz&Hymes, 1972; Erickson, 1989, 2007; Heinrichsmeier, 2022).
Keywords: language pedagogy; indigenous schools; Mexico; multilingualism; qualitative and time-based action cycles of communicative tasks; ethnographic microanalysis